(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2025)
An analysis of the essence of the mechanism for ensuring the rights, freedoms and legitimate interests of individuals at the stage of pre-trial investigation has been carried out, taking into account contemporary challenges, in particular the digitalisation of legal relations, the impact of extraordinary legal regimes (martial law) and the integration of international legal standards into national legislation. The author’s vision of the structure of the mechanism for ensuring the rights, freedoms and legitimate interests of individuals, which includes both preventive and restorative guarantees, is proposed. Emphasis is placed on the need for their flexible adaptation to the latest social and legal realities. The expediency of expanding traditional approaches to understanding this mechanism by combining formal (procedural) guarantees with real instruments for their practical implementation is substantiated, which allows for a high level of human rights protection to be achieved. It has been proven that the mechanism for ensuring the rights, freedoms and legitimate interests of individuals at the pre-trial investigation stage is a complex, multi-level system that requires a comprehensive approach to the protection of human rights. It has been established that the effectiveness of the mechanism for ensuring rights and freedoms at the stage of pre-trial investigation is determined not only by the existence of relevant norms, but also by the effectiveness of controlling and supervisory institutions, the ability of the system to respond to new challenges and ensure a balance between the interests of the state, society and the individual. The mechanism for ensuring the rights, freedoms and legitimate interests of individuals at the pre-trial investigation stage has been defined as a comprehensive, multi-level system of interrelated regulatory, organisational, procedural, control and value elements that are integrated to ensure the effective guarantee, protection and defence of individual rights and freedoms, as well as to respond promptly to violations in criminal proceedings. It has been established that further improvement of the mechanism for ensuring the rights, freedoms and legitimate interests of individuals at the pre-trial investigation stage should be based on the interaction of legal, institutional and technological innovations, the formation of a culture of respect for human rights and the strengthening of the responsibility of state bodies for compliance with these standards.